Wheat straw availability for bioenergy in England - Townsend, T.J.; Sparkes, D.L.; Ramsden, S.J.; Glithero, N.J.; Wilson, P. (Elsevier, 2018)
In an effort to meet energy demands while reducing carbon emissions, crop residues, such as wheat straw, have been investigated for their use as feedstock for biofuel production. In order to identify the feasibility of utilising crop residues as bioenergy feedstock, a postal survey was conducted to determine current farm business wheat straw use, destination and potential future supply. The survey responses showed a bias towards larger, more commercially-minded farms, therefore capturing a large area of straw production. Results demonstrated a wide range of responses to both current straw use and potential for the supply of straw to different markets in the future. Interestingly, even for a very generous payment for straw, 28.5% of straw currently chopped and incorporated would not be sold, suggesting that straw supply for bioenergy feedstock is likely to be more limited than previously assumed. However, higher prices for straw would encourage farmers to explore ways of increasing straw yield.